leadership and communication delegates and admission to subdeledates new degree program in psychology university Universidad Centroccidental Lisandro Alvarado (Revista Electrónica REDINE, 2018)
The present study was aimed to strengthen leadership and communication of delegates and subdelegados new to the Bachelor Program in Psychology at the University Centroccidental "Lisandro Alvarado". The same was framed in the qualitative paradigm approach under socio - critical. Mode Participatory Action Research, which follows the qualitative perspective and is frequently recommended in the educational context was used. We worked with twenty-eight (28) stakeholders who participated in the development of the scheduled sessions. The research design was organized into five stages: diagnosis, preparation of the action plan, implementing the plan, assessment of evidence plan executed action and its impact on the development of leadership and communication, and the fifth time replanning. The collection of information is performed using the techniques of participant observation, focused testimonies, interviews and focus group discussions. For the analysis and evidence interpretation of ATLAS.ti version 6, whereby the systematic categorization of content, was obtained. Then he reflected on the importance of initiating a process of innovation and transformation of the contents provided in the areas of personal development of the learner.  It was also recommended that a program orientation discovery and exploration of skills in the area of leadership, communication and conflict resolution, which allow the student to integrate the knowledge acquired to the applicability thereof to the professional field.
Keywords: leadership; communication; delegates and subdelegados incoming